Clinical characteristics, surgical management, and prognostic factors for supratentorial hemangioblastoma: A retrospective study - Chen, Long; Xiong, Zujian; Zhou, Yian; Li, Yanwen; Xie, Yuanyang; Xiong, Yi; Wanggou, Siyi; Li, Xuejun (Frontiers in Surgery, 2023)
Background Supratentorial hemangioblastoma is an extremely rare neoplasm. The aim of this study is to delineate the clinical features among cystic and solid supratentorial hemangioblastoma patients and evaluate the risk factors for progression-free survival (PFS). Methods We conducted a literature search in PubMed for histopathologically identified supratentorial hemangioblastoma between 1947 and 2021 and extracted and collected the clinical features of patients treated at our own institute. The rate of PFS was determined using Kaplan–Meier analysis. Differences in categorical factors, such as the location of tumor and diagnosis of von Hippel–Lindau disease, were analyzed using the Pearson χ2 test. A Cox regression analysis was performed to evaluate the association between various variates and survival outcomes. Results A total of 237 cases of supratentorial hemangioblastoma were identified from 169 studies. A survival analysis found that patients with cystic tumors had a significantly better prognosis than those with solid tumors (log-rank, p = 0.0122). Cox regression analysis suggested that cystic hemangioblastoma (hazard ratio (HR): 0.186, 95% CI: 0.043–0.803, p < 0.05) and gross total resection (GTR) (HR: 0.126, 95% CI: 0.049–0.323, p < 0.001) were significant predictors of longer survival (PFS) for supratentorial hemangioblastoma. Following an analysis of 13 supratentorial hemangioblastoma cases from our institute, we validated that cystic tumor had improved prognosis than solid tumor (log-rank, p = 0.0096) and GTR was superior to subtotal resection (log-rank, p = 0.0029). Conclusions Cystic hemangioblastoma vs. solid hemangioblastoma may be two tumoral statuses with different clinical features, and a specific treatment strategy should be considered.